2009
DOI: 10.1053/j.gastro.2009.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of TRPC3 in Mice Reduces Store-Operated Ca2+ Influx and the Severity of Acute Pancreatitis

Abstract: Background and Aims-Receptor-stimulated Ca 2+ influx is a critical component of the Ca 2+ signal and mediates all cellular functions regulated by Ca 2+ . However, excessive Ca 2+ influx is highly toxic resulting in cell death, which is the nodal point in all forms of pancreatitis. Ca 2+ influx is mediated by store-operated channels (SOCs). The identity and function of the native SOCs in most cells is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 40 publications
8
139
0
3
Order By: Relevance
“…Our findings that blockade of intracellular Ca 2ϩ reduced calcineurin activation are in general agreement with previous reports that sustained Ca 2ϩ signals are required to activate calcineurin (22,23 (12,25,46), Ca 2ϩ store depletion, and the subsequent opening of store operated Ca 2ϩ entry (SOCE) channels (47)(48)(49).…”
Section: Discussionsupporting
confidence: 82%
“…Our findings that blockade of intracellular Ca 2ϩ reduced calcineurin activation are in general agreement with previous reports that sustained Ca 2ϩ signals are required to activate calcineurin (22,23 (12,25,46), Ca 2ϩ store depletion, and the subsequent opening of store operated Ca 2ϩ entry (SOCE) channels (47)(48)(49).…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, the production of DAG may be insufficient to activate TRPC3 and PKC in immature B cells, since it has been reported that an increase of intracellular Ca 2+ and hydrolysis of PtdIns(4,5)P 2 are induced in response to BCR cross-linking in mature B cells but an increase of intracellular Ca 2+ levels is induced in the relative absence of PtdIns(4,5)P 2 hydrolysis in immature B cells (King and Monroe, 2000). These aspects can be addressed using TRPC3 knockout mice, in which B-cell function has not been demonstrated yet (Hartmann et al, 2008;Kim et al, 2009). Interestingly, our preliminary results demonstrated that application of the TRPC3-selective inhibitor Pyr3 (Kiyonaka et al, 2009) suppressed BCR-induced Ca 2+ responses, sustained PKC PM translocation, and ERK activation in murine primary splenic B cells (T.N., unpublished data).…”
Section: +mentioning
confidence: 87%
“…During the last 20 years, the family of TRPC (canonical transient receptor potential) channels has been proposed as candidates for SOCE. Number of reports has shown a reduced SOCE activity when TRPC expression was knocked down or knocked out [8][9][10][11]. When exogenously expressed some TRPC channels displayed SOCE activity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%